Retrobulbar/intraconal tube placement in patients with glaucoma: Ahmed FP-7 and tube extender case series with 1 year follow-up - Laroche, Daniel; Grodecki, Brian; Grimes, Kara Rickford; Ng, Chester (Frontiers in Ophthalmology, 2025)
PurposeThe Ahmed FP-7 valve is useful in the management of refractory glaucoma. However, this can often have ocular hypertensive phase and subconjunctival fibrosis that can lead to increased medication use and failure. We report how retrobulbar and intraconal plate placement with tube extension can avoid the ocular hypertensive phase, lower intraocular pressure, and reduce medication burden.Patients and methodsThis is a retrospective case series of 4 patients with glaucoma who underwent Ahmed FP-7 valve and retrobulbar/intraconal tube placement with a one-year follow-up.ResultsOne-year results in 4 patients with advanced glaucoma and pseudophakia revealed a pre-operative intraocular pressure of 21 mmHg on 5.5 medications. At one year, the post-operative intraocular pressure was 10.25 on 0 medications. The vision and visual fields were stable. One patient required drainage of a choroidal effusion and one patient required burping of viscoelastic on post-operative day one.ConclusionsThe combined insertion of the Ahmed FP-7 valve and silicone tube inserted into the retrobulbar/intraconal space has been shown to prevent ocular hypertensive phase, lower intraocular pressure, and reduce medication burden at one year.